Efficient Hybrid DCT-Domain Algorithm for Video Spatial Downscaling. (10th September 2007) - Roma Roma, Nuno Nuno; Sousa Sousa, Leonel Leonel
Abstract : A highly efficient video downscaling algorithm for any arbitrary integer scaling factor performed in a hybrid pixel transform domain is proposed. This algorithm receives the encoded DCT coefficient blocks of the input video sequence and efficiently computes the DCT coefficients of the scaled video stream. The involved steps are properly tailored so that all operations are performed using the encoding standard block structure, independently of the adopted scaling factor. As a result, the proposed algorithm offers a significant optimization of the computational cost without compromising the output video quality, by taking into account the scaling mechanism and by restricting the involved operations in order to avoid useless computations. In order to meet any system needs, an optional and possible combination of the presented algorithm with high-order AC frequency DCT coefficients discarding techniques is also proposed, providing a flexible and often required complexity scalability feature and giving rise to an adaptable tradeoff between the involved scalable computational cost and the resulting video quality and bit rate. Experimental results have shown that the proposed algorithm provides significant advantages over the usual DCT decimation approaches, both in terms of the involved computational cost, the output video quality, and the resulting bit rate. Such advantages are even more significant for scaling factors other than integer powers of 2 and may lead to quite high PSNR gains.